Fatores mediadores do processo de colaboração entre universidade e empresa para a realização de projetos de P&D: aplicação a um Centro de Tecnologia em Nanomateriais - Raissa Guerra Resende (2018)
In a knowledge-based economy, universities are increasingly seen as strategic partners by companies that need to innovate to ensure long-term prosperity. Due to that, interaction mechanisms between Universities and Enterprises (U-E), such as collaborative Research and Development (R&D) projects, emerge as ways of promoting this interface. However, the execution of a R&D project is only one phase of the collaboration process, since much must be done to make it happen. Aware of the criticality of the prior phases to the execution of R&D projects for the establishment of U-E partnerships, the main goal of this study is to answer the following question, through a Technology Center (TC) perspective: which mediating elements are present and how is their influence perceived in the effectiveness of U-E partnerships, for the establishment of collaborative R&D projects in a TC of a federal public university? With the purpose of answering this question, semi structured interviews with questionnaire were made as methodological strategy. The interviews were carried out with collaborators of current and potential enterprise partners, TC researches and people related to consolidation of R&D collaborative projects. Data collection and analysis used an adaptation of Kano´s Method to the context of U-E relationships. Results has shown that mediating elements related to the way of interaction among individuals — such as trust, share information beyond the project, company and university champions, contractual negotiations —, as well as those related to the university group technical and scientific competences — reputation and repercussion, finished projects, among others — are critical to collaborative R&D projects between the U-E exist. However, interviews indicated that for the establishment of these projects, the influence and importance attributed by the companies to mediating elements related to interpersonal aspects is considerably higher than that considered by the university. Based on these findings, as well as the use of unconventional methods and techniques in this study field, this paper aims to enrich studies in interinstitutional relations field and other open innovation contexts. Moreover, it intends to contribute to the establishment of R&D collaborative projects at the present TC, and broadly, for setting up more and better U-E partnerships in Brazil.